Activity аnd Danger of Avalanche-Talus Processes on the Territory of the Kabardino-Balkarian Republic - V. V. Razumov; R. O. Kalov; N. D. Bogdanova; N. V. Razumova; N. G. Likhovid (Наука. Инновации. Технологии, 2023)
Introduction. On the territory of the Kabardino-Balkarian Republic, avalanche-talus processes have become widespread mainly in the mountainous regions of the republic. The article provides an assessment of the extent, activity and danger of avalanche-talus processes on the territory of the republic for 2005–2022.Materials and research methods. The key method used in this work was the analysis of various materials containing information on the activity of the manifestation of avalanche-talus processes on the territory of the Kabardino-Balkarian Republic. Literature sources, reports and published data of the Center for State Monitoring of the State of the Subsoil of the Federal State Budgetary Institution “Hydrospetsgeology” for 2005–2022 were used as the main ones.Research results and their discussion. The authors characterize the conditions and causes, the extent of the spread, and also assess the activity and danger of avalanche-talus manifestations that occurred on the territory of the Kabardino-Balkarian Republic in 2005–2022. The paper provides information on the extent of destruction and deformation of settlements and economic objects under the influence of these processes.Conclusions. Information is given on the location of avalanche-talus manifestations on the territory of the Kabardino-Balkarian Republic and their characteristics, the extent of destruction and deformation caused by them. During the studied period of time, about 120 significant landslide-talus manifestations were recorded on the territory of the republic, the volumes of which, in most cases, did not exceed 200–250 m3, the largest landslides reached 30 thousand m3. The largest scale of landslide-talus activity was noted in 2006 and 2008, and a very weak degree of activation was observed in 2015 and 2020. The majority of active landslide-talus sites (more than 90%) were recorded on the highways of the republic. The most significant degree of their activation was noted in the Chegem and Elbrus administrative districts of the republic.